Throughput Maximization method of Cognitive Radio system for Energy Harvesting - Shelesh Krishna saraswat, (International Journal of Advanced Science and Technology, 2020)
In current scenario of wireless communication cognitive radio is a best solution to deal with spectrum scarcity. In cognitive radio networks, spectrum unutilized frequency to allow secondary users for the primary user. However the pursuance of spectrum sensing based on fusion rule and sensing time, when the Cooperative Spectrum Sensing applied to the Primary Users activity. In cognitive radio, throughput is a utility of channel condition, sensing time and harvesting energy. Co-operative spectrum sensing is a method that will enhance the  probability of detection and minimise false alarm . When primary user not detected then by using the cognitive radio metod they are capable to intellect and access the frequency spectrum band. We take both spectral efficiency and energy efficiency in to consideration cooperative sense information to enhance the sensing of cognitive radio by energy harvesting. To determine an best spectrum sensing strategy that improve throughput although fulfilling the energy causality constraints and sense principal user constraints. Our proposed work, we have addressed the issue of throughput maximization by optimally selecting the charging time of battery in cognitive radio. We have developed a solution used for cooperative spectrum  using AND rule, OR rule. It has been deduced by extensive simulation grades that k-out-of N rule optimize the system throughput in better way compared to other co-operative method at different channel condition and harvesting energy for optimum selected charging time.